Meningkatkan Motivasi dan Hasil Belajar IPA Melalui Strategi STAD Pada Siswa Kelas IV SD Negeri Pilangrejo 1 Boyolali Tahun 2015/2016 - Pamungkas, Betty Tri (2016)
Classroom action research is conducted to improve the study process which is still not optimal. The problems occured in the school which can be seen among the students especially in science subject are lack of motivation and low study achievement. Thus, this research aims(1) To improve 4th grade students's motivation in learning science, (2) To improve 4th grade student's study achievement in science subject. This research of class procceding. This research is divided into four stages in each cycle. There are planning, acting, observing and reflecting. Research of class procedding is carried out in SD Negeri Pialngrejo 1 Boyolali, particularly students in the 4th grade, year of study 2015/2016 which has 30 students. This research consists of two cycles. Each cycle consists of two meetings which is approximately (4x35 minutes). Based on the results of the research and keen observation during research of class procedding toward student's motivation from pra-cycle, cycle I and cycle II are showing improvement. The result is marked with some motivation indicators: (1) Student's desire and will to success in learning science are 30%, 56,67% and 85%, (2) Student's encouragement and need to have activities are 33,33%, 55% and 76,65%, (3) Student who show enthusiasm are 20%, 41,67% and 78,34%. Meanwhile, the result which came from pra cycle stage, cycle I, and cycle II are 56,67%, 76,67% and 86,67%. It can be concluded that the the application of STAD strategy in science subject can improve motivation and study achievement of 4th grade students in SD Negeri Pilangrejo 1 Boyolali, year of study 2015/2016.